2009
DOI: 10.1007/s00384-009-0724-0
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 gene polymorphisms and haplotype analysis in colorectal cancer

Abstract: These results suggested that three studied SNPs of ABCB1 were located in one haplotype block. Differences in ABCB1 (1236C>T) and ABCB1 (2677G>T/A) genotypes and T(1236) allele distribution between investigated populations indicate significant impact of these SNPs on risk of development of colorectal cancer. Polymorphism ABCB1 (3435C>T) may be a prediction marker of cancer chemotherapy effectiveness. Differences in haplotype distributions between colorectal cancer patients and healthy population suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 45 publications
2
47
2
Order By: Relevance
“…This was inconsistent with most other studies [13][14][15][16][17][18][19][20][21][22]. In this meta-analysis the results when stratified for ethnicity or population source, indicated no association between ABCB1 rs1045642 SNPs and CRC.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This was inconsistent with most other studies [13][14][15][16][17][18][19][20][21][22]. In this meta-analysis the results when stratified for ethnicity or population source, indicated no association between ABCB1 rs1045642 SNPs and CRC.…”
Section: Discussioncontrasting
confidence: 73%
“…As there was no evidence of heterogeneity among four studies for ABCB1 rs2032582 SNPs and CRC risk,a fixed-effect model was used [16,[19][20][21]. There was no significant association between Three studies supplied data on the frequency for combinations of two SNPs of the ABCB1 gene, including only wild-type alleles (rs2032582G/rs1045642C), only mutated alleles (rs2032582T/rs1045642T), and mixed alleles (rs2032582G/rs1045642T and rs2032582T/ rs1045642C) [19][20][21]. No evidence of heterogeneity existed among these studies for the above allele model with the exception for rs2032582T/ rs1045642T.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Bandur et al [53] reported that wild type haplotype of these three SNPs increases the risk of acute rejection of the graft in renal transplant patients. Some clinical studies have shown that 1236T-2677T-3435T haplotype is associated with reduced P-gp expression and activity [54], and in this manner Panczyk et al [55] confirmed greater risk for colorectal cancer development in population with TTT haplotype. Sai et al [56] associated this mutant haplotype with poorer irinotecan clearance in various cancers.…”
Section: Discussionmentioning
confidence: 88%
“…The C3435T polymorphisms did not correlate with early relapse in high-risk stage II and stage III colorectal cancer patients [9], and G2677T/A and C3435T polymorphisms did not correlate with long-term prognosis in stage II-B or III-C colorectal cancer patients treated with 5-FU/leucovorin [10]. In contrast, they have been shown to be a predictive biomarker of 5-FU-based treatment effectiveness [8]. However, few studies have focused on toxicity, despite the fact that toxicity is generally related to efficacy.…”
mentioning
confidence: 96%
“…Some of the most commonly studied variants are rs1128503 (C1236T), rs2032592 (G2677A/T) and rs1045642 (C3435T) and the most commonly-studied haplo type involves these three SNPs. Significant differences in haplotype distributions were found between colorectal cancer patients and a healthy population [8]. To date, there is no clear consensus on the impact of any of these variants on Aim: To find out whether SNPs in the transporter gene ATP-binding casette B1 (ABCB1) were related to adverse effects in colorectal cancer patients treated with 5-fluorouracil (5-FU) or capecitabine.…”
mentioning
confidence: 99%